3(q-1)+7=3q+4

Simple and best practice solution for 3(q-1)+7=3q+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(q-1)+7=3q+4 equation:


Simplifying
3(q + -1) + 7 = 3q + 4

Reorder the terms:
3(-1 + q) + 7 = 3q + 4
(-1 * 3 + q * 3) + 7 = 3q + 4
(-3 + 3q) + 7 = 3q + 4

Reorder the terms:
-3 + 7 + 3q = 3q + 4

Combine like terms: -3 + 7 = 4
4 + 3q = 3q + 4

Reorder the terms:
4 + 3q = 4 + 3q

Add '-4' to each side of the equation.
4 + -4 + 3q = 4 + -4 + 3q

Combine like terms: 4 + -4 = 0
0 + 3q = 4 + -4 + 3q
3q = 4 + -4 + 3q

Combine like terms: 4 + -4 = 0
3q = 0 + 3q
3q = 3q

Add '-3q' to each side of the equation.
3q + -3q = 3q + -3q

Combine like terms: 3q + -3q = 0
0 = 3q + -3q

Combine like terms: 3q + -3q = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 8y-y=-45 | | 9-2=x+9 | | 27+x-3x+47=x+26-10 | | 27+x+3x+47=x+26+10 | | z=0.33 | | 9x(x+1)=0 | | 9x-7=5(2x-3) | | 9p+6=5p-2 | | 0=2x^3+6x^2-5 | | 42=31-3c | | 2(3x+4)=30 | | 7t=t | | 6-2[3-5(4-7)]= | | 3+2w=25 | | 8q-10q=4 | | 220+.25x=445 | | 500+90*x=5000 | | 2-5(2-5)= | | 500+90=5000 | | (-6)(-6)(-6)= | | 4y+5x+x-y= | | 36(-6)= | | -9y=2 | | 4+7-(3-2)= | | 2+3x-x+4x= | | U-24=-7 | | 4d+15=120 | | -67=6v-1 | | 4+7(3*2)= | | -4m-9=19 | | 17x+29=114 | | 13=5-8e |

Equations solver categories